Internationalization process of large-sized firms : Evidence from Malaysia - Jannatul Firdaus, Ismail (2011)
International expansion is an initial strategy for firms particularly from emerging countries like Malaysia to be in the global market to deeply engage in a process known as internationalization. The internationalization process among firms from emerging countries depicts some variances from developed countries due to the internal and external differences between them. There were some patchy and qualitative evidences on internationalization of emerging firms but there remains insufficient in providing a conclusive model. This research attempts to fill up the gap by contributing some empirical evidences quantitatively which is exceptionally limited, on the internationalization process or firms from emerging countries. Generally, this study endeavors to examine the internationalization process of Malaysian firms into foreign markets by focusing on the firms' internationalization advantage. intensity and their effects on the entry mode and foreign market selection. Specifically, this study aims to determine the relationship between internationalization advantage and internationalization intensity; identify the effect or mediating and moderating forces between internationalization advantage and internationalization intensity: and finally propose an internationalization framework for Malaysian firms to formulate their international expansion strategy. Quantitative method was adopted through a survey by using questionnaires to firms that were sampled from the Malaysia Bourse (BM) directory. 100 companies participated in the study. Regression and Hierarchical nMultivariate Regression Analyses (HMRA) were utilized to examine the hypotheses and hierarchical regression analyses were conducted in analyzing the moderating role of motivation and network as well as mediating role of barriers between internationalization advantage and internationalization intensity. The research found that there is a relationship between firms' internationalization advantage to go abroad and their internationalization intensity. The findings also suggest that motivation and network can intervene the firms' internationalization process while barriers can temperate the process. This study also indicates that barriers moderate the internationalization before and after the process had taken place. 'This study highlights the internationalization process of Malaysian firms which represent emerging countries which has been neglected by internationalization theories developed in industrialized economies.